(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
In India low back ache is one of the most common emerging diseases which are affecting day to day life of people physically as well as psychologically. Low back ache is the second most common disorder causing disability. Among its various causes the most commonly appearing one is Sciatica. Sciatica is a condition in which pain starts from low back and radiates to leg mostly unilateral but in some, it may be bilateral also. In Ayurvedic perspective its features resemble to those of Gridhrasi. In Ayurvedic classics two types of Gridhrasi have been described namely Vataja and Vata-kaphaja. The case study being presented is of a 44yr old male patient suffering from Vataja gridharsi. Basti karma is the choice of treatment in cases of Gridhrasi where as Snehana/ Snigdha svedana is choice of treatment for any Vataja disorder. So, Panchakarma therapy in this case includes Patrapindasveda, Sarvang vashpasveda and Basti therapy along with oral medication assessed on the basis of Oswestry disability index. The results indicate that the patient improved in presenting features up to 68.75% as well as day to day activities were also performed effectively by him.